Analisis Model Pengukuran Human Capital dalam Organisasi - Cecep Hidayat (Binus Business Review, 2013)
Measurement of human capital is not an easy to do because it is dynamic and always changing in accordance with the changing circumstances. Determination of dimensions and indicators of measurement needs to consider various factors such as situations and also the research scopes. This article has objectives to review the concepts, dimensions and measurement models of human capital. The research method used was literature study with a major reference source from current journal articles that discuss the measurement of human capital. Results of the study showed that basically the definition set forth in any dimension containing either explicitly or implicitly. In addition, the result indicated that there are three main categories of equality among researchers regarding the definition of human capital which emphasizes on: economic value/productivity, education, and abilities/competencies. The results also showed that the use of definitions, dimensions, and indicators for measurement of human capital depends on the situation, the scope of research, and the size of the organization. The conclusion of the study indicated that the measurement model and determination of dimensions and indicators of human capital measurement will determine the effectiveness of the measurement, and will have an impact on organizational performance.